1978
DOI: 10.1139/m78-146
|View full text |Cite
|
Sign up to set email alerts
|

The effect of compounds which degrade hydrogen peroxide on the enumeration of heat-stressed cells of Salmonella senftenberg

Abstract: Greater than 90% of heat-stressed cells of Salmonella senftenberg failed to grow on trypticase soy agar. Adding to this medium compounds which are capable of degrading hydrogen peroxide allowed growth of the heat-injured cells. These compounds did not stimulate growth of heated cells of Streptococcus faecium, an organism which does not possess catalase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
3

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 0 publications
2
36
3
Order By: Relevance
“…Catalase addition did not affect the culturability of untreated cells. Furthermore, the addition of sodium pyruvate, a compound that degrades H 2 O 2 (28,30,38), to the surfaces of LB agar plates also increased the number of CFU obtained from TCE-treated cells (data not shown).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Catalase addition did not affect the culturability of untreated cells. Furthermore, the addition of sodium pyruvate, a compound that degrades H 2 O 2 (28,30,38), to the surfaces of LB agar plates also increased the number of CFU obtained from TCE-treated cells (data not shown).…”
Section: Resultsmentioning
confidence: 96%
“…From studies performed primarily within the context of food microbiology and public health, it is known that catalase and pyruvate can increase the enumeration of physically or chemically injured bacteria on agar plates (5,28,30). It is thought that catalase and pyruvate act by preventing the accumulation of H 2 O 2 in and/or around injured cells, which, in contrast to healthy cells, are apparently unable to tolerate even low levels of this reactive oxygen species (28,38). In this study, we found that the addition of catalase or sodium pyruvate to the surfaces of the LB agar plates increased the culturability of TCE-treated cells of B. cepacia G4 by as much as 100-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Since one known effect of sodium pyruvate on microbiological media is to degrade hydrogen peroxide (3,7,14,16,17,18,29), the possibility that a hydrogen peroxide-sensitive population of culturable cells had formed in the cold ASW was investigated. Catalase, an enzyme which breaks down hydrogen peroxide, was added to HI plates by surface spreading.…”
Section: Resultsmentioning
confidence: 99%
“…A plating assay revealed that the culturable cells from middle time points in the studies were much more sensitive to hydrogen peroxide than fresh HI broth-derived cells. Supplementation of HI plates with either sodium pyruvate or catalase, agents which degrade hydrogen peroxide (3,7,14,16,17,18,29), yielded higher colony counts. However, there was also a continued decline to complete loss of these culturable cells (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation